Deterioration Patterns on Engineering Properties of Hipparion Red Clay under Acid Rain Conditions - Lv, Gaijie (Journal of Progress in Civil Engineering, 2025)
Acid rain significantly affects the properties of cohesive soils, and it is a major factor contributing to subgrade diseases in cohesive soil areas. Studying the deterioration patterns on engineering properties of cohesive soils under acid rain conditions is of great engineering significance for subgrade design in such regions. By configuring solutions with different pH values to simulate acid rain erosion on Hipparion red clay, expansion tests, shear tests, and permeability tests were conducted to analyze influencing factors and their extent. The results show that the macroscopic properties of Hipparion red clay deteriorate in acidic environments, including increased expansibility, reduced shear strength, and enhanced permeability. The extent of these deteriorations is related to the dry density of the soil sample and the pH value of the solution. Under the same dry density conditions, the deterioration of macroscopic properties increases as the pH value decreases. Under the same pH conditions, the deterioration of macroscopic properties decreases as the dry density increases. Compaction control of Hipparion red clay in acidic environments has a significant impact on the soil samples. Analysis shows that when the compaction degree reaches about 94%, the impact of acid rain on Hipparion red clay is minimized.